2018
DOI: 10.1080/22201181.2018.1444443
|View full text |Cite
|
Sign up to set email alerts
|

Intra-articular dexmedetomidine with bupivacaine versus bupivacaine alone for postoperative analgesia after knee arthroscopy

Abstract: Background: Optimal relief of pain after knee arthroscopy is essential for early rehabilitation and mobilisation and to minimise postoperative morbidity. This study's aim was to assess dexmedetomidine as an additive to intra-articular (IA) bupivacaine in terms of analgesic duration and postoperative rescue analgesic consumption following arthroscopic knee surgery. Methods: A total of 70 patients, ASA physical status I and II, undergoing knee arthroscopy under general anaesthesia were enrolled in this double-bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Shaimaa FM and colleagues assessed the effects of dexmedetomidine as an adjuvant to bupivacaine on pain scores and analgesic consumption [2]. In that double-blind randomized controlled study, dexmedetomidine as an adjunct to local anesthetic was found to prolong the analgesic duration and decrease the postoperative analgesic requirement [2].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Shaimaa FM and colleagues assessed the effects of dexmedetomidine as an adjuvant to bupivacaine on pain scores and analgesic consumption [2]. In that double-blind randomized controlled study, dexmedetomidine as an adjunct to local anesthetic was found to prolong the analgesic duration and decrease the postoperative analgesic requirement [2].…”
Section: Discussionmentioning
confidence: 99%
“…Shaimaa FM and colleagues assessed the effects of dexmedetomidine as an adjuvant to bupivacaine on pain scores and analgesic consumption [2]. In that double-blind randomized controlled study, dexmedetomidine as an adjunct to local anesthetic was found to prolong the analgesic duration and decrease the postoperative analgesic requirement [2]. The researchers underlined the safety concerns about local adverse effects on chondrocytes and concluded that these effects should be clarified before making any recommendation about the drug [9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The sample size was determined by taking the total consumption of rescue analgesia in milligrams in 24 hours with reference to the study by Mostafa et al [18]. The reference study was done with 42 patients.…”
Section: Sample Size Calculationmentioning
confidence: 99%